Integrasi Edukasi Gizi, Keamanan Pangan, dan Inovasi Olahan Ikan Lokal dalam Upaya Pencegahan Stunting di Kampung Ramsai, Lampung: Integration of Nutrition Education, Food Safety, and Local Fish-Based Food Innovation to Prevent Stunting in Ramsai Village, Lampung - Anggarkasih, Made Gayatri; Dianah, Rosyda; Fatimah, Ai Imas Fasidoh; Suhaima, Nurafi Razna (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Stunting remains a significant public health issue in Indonesia, necessitating cross-sectoral interventions, particularly at the community level. The NUTRIFISH Community Engagement Program was implemented in Ramsai Village, Way Tuba District, Way Kanan Regency, as an integrated initiative to promote nutrition and food safety through education and empowerment. The program involved collaboration among academics, local government, community health cadres, and early childhood education institutions, utilizing an interactive and participatory approach. The activities began with online coordination meetings and trial production of tilapia fish nuggets, followed by an official meeting with local authorities and a series of training sessions on balanced nutrition, household food safety, and fish-based food processing. Evaluation was conducted using online questionnaires via Google Form. Results indicated that the most perceived impact was improved knowledge of balanced nutrition (34%), followed by strengthened multi-stakeholder collaboration (19%) and increased adoption of fish nugget innovations (17%). Additional impacts included greater awareness of food safety and stunting prevention (15% each). The program was well received, with participants stating that it was implemented very effectively. These outcomes underscore the effectiveness of a community-based educational approach and present opportunities for sustainability through the development of a local cadre and strengthened stakeholder collaboration.